1969
DOI: 10.1136/bmj.3.5672.690
|View full text |Cite
|
Sign up to set email alerts
|

Selective Vagotomy without Drainage. An Interim Report

Abstract: Rundles (1945), who, in discussing the oesophageal changes, considered that the whole problem was a challenge. Mandelstam and Leiber (1967) concluded that the oesophageal motor dysfunction was a common finding in diabetic neuropathy-gastroenteropathy, and that on occasion it results in dysphagia. In their group 12 had oesophageal dysfunction but only three had symptoms, while their control group had no changes at all.The present study indicated that abnormal oesophageal function was not limited to one group a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1970
1970
1974
1974

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…In man, preservation of an innervated antrum in the acid stream was pioneered successfully by Ferguson, Billings, Swensen, and Hoover (1960 Holle, 1967) in which the antrum has been left innervated in several hundred patients; but it appears that a concomitant drainage procedure or resection is invariably added. Bilateral selective vagotomy without a drainage procedure has been used by Burge, MacLean, Stedeford, Pinn, and Hollanders (1969) in treating more than IOO selected cases of duodenal ulceration. Studies of gastric emptying (Shiina and Griffith, 1969) and motility (Wohlrabe and Kelly, 1959; Stavney, Kato, Griffith, Nyhus, and Harkins, 1963) in dogs subjected to bilateral selective vagotomy without drainage suggest, however, that antral motility is much reduced and that gastric stasis is severe in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…In man, preservation of an innervated antrum in the acid stream was pioneered successfully by Ferguson, Billings, Swensen, and Hoover (1960 Holle, 1967) in which the antrum has been left innervated in several hundred patients; but it appears that a concomitant drainage procedure or resection is invariably added. Bilateral selective vagotomy without a drainage procedure has been used by Burge, MacLean, Stedeford, Pinn, and Hollanders (1969) in treating more than IOO selected cases of duodenal ulceration. Studies of gastric emptying (Shiina and Griffith, 1969) and motility (Wohlrabe and Kelly, 1959; Stavney, Kato, Griffith, Nyhus, and Harkins, 1963) in dogs subjected to bilateral selective vagotomy without drainage suggest, however, that antral motility is much reduced and that gastric stasis is severe in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal gastric vagotomy denervates the acidsecreting area of the stomach but preserves the innervation to the gastric antrum. Burge, MacLean, Stedeford, Pinn, and Hollanders (1969) suggested that a drainage procedure was not necessary with selective vagotomy in the absence of duodenal stenosis.…”
mentioning
confidence: 99%
“…It soon became clear that there were many complications resulting from gastric retention (Jackson, 1948;Slaney et al, 1956), and Dragstedt et al (1947) were quick to point out that most patients with duodenal ulcer required some form of drainage operation in addition to vagotomy. Burge et al (1969) suggested that selective vagotomy would retain sufficient innervation to the prepyloric and pyloric regions of the stomach via the pyloric branch of the anterior vagus and so allow normal gastric emptying to occur. Nevertheless, Franksson (1948) had earlier attempted to use bilateral selective vagotomy without drainage, but because of the complications of gastric retention, even in patients with no ulcer stenosis, he later abandoned the operation (Shiina and Griffiths, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…The operative technique used for selective vagotomy was similar to the technique described by Burge et al (1969), with careful preservation of both the coeliac and the hepatic branches of the vagus nerves. Ten patients were from Birmingham and five from Liverpool: all were men aged 21 to 63 years.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation